2004
DOI: 10.1161/01.res.0000111522.02730.56
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization and Functional Effects of P 21 -Activated Kinase-1 (Pak1) in Cardiac Myocytes

Abstract: Abstract-We investigated intracellular localization and substrate specificity of P 21 -activated kinase-1 (Pak1) in rat cardiac myocytes. Pak1 is a serine/threonine protein kinase that is activated by Rac1/Cdc42 and important in signaling of stress responses. Yet the localization and in vivo function of Pak1 in heart cells is poorly understood. Studies reported here indicate that Pak1 physically interacts with protein phosphatase 2a and localizes to the Z-disk, cell membrane, intercalated disc, and nuclear mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(153 citation statements)
references
References 43 publications
6
147
0
Order By: Relevance
“…Interestingly, Pak1 is also associated with the sarcomere. In fact, Pak1 has been shown to localize to the sarcomeric Z disc, 81 though a precise role for Pak proteins in sarcomeric structure has not been defined.…”
Section: Developmental Functions Of Pak Kinases As Assessed By Studyimentioning
confidence: 99%
“…Interestingly, Pak1 is also associated with the sarcomere. In fact, Pak1 has been shown to localize to the sarcomeric Z disc, 81 though a precise role for Pak proteins in sarcomeric structure has not been defined.…”
Section: Developmental Functions Of Pak Kinases As Assessed By Studyimentioning
confidence: 99%
“…However, it may not have a direct effect on myofilament proteins, since myofilament protein phosphorylation was reported to be preserved in transgenic mouse models with altered calcineurin activity (Wilkins and Molkentin 2002). However, hypophosphorylation of several myofilament proteins has been attributed to PP1 and 2A (Ke et al 2004;Humphries et al 2002;Wu and Solaro 2007). Oxidative stress activates stress kinases, such as several PKC isoforms, PKD, CaMKII and P38 mitogen-activated protein kinases and inactivate PP1 and/or PP2A activity (Jin Jung et al 2013).…”
Section: Contribution Of Oxidative Stress To Pathology In Muscular Dymentioning
confidence: 99%
“…54 Buscemi et al 25 found that phosphorylation of cTnI Ser149 by PAK3 was accompanied by an increase in the Ca 2þ sensitivity of myofilament force development. A study by Ke et al 55 found that, although PAK1 could phosphorylate cTnI in vitro, adenovirus infection of isolated myocytes with a constitutively active PAK1 construct decreased the overall phosphorylation status of cTnI and increased the Ca 2þ sensitivity of force production. 55 Because phosphorylation status of individual cTnI sites was not assessed in that study, it is not known if some sites underwent increased phosphorylation while others exhibited a proportionally greater decrease in dephosphorylation.…”
Section: Physiological Implications Of Phosphorylation At Ser22ser23 mentioning
confidence: 99%
“…A study by Ke et al 55 found that, although PAK1 could phosphorylate cTnI in vitro, adenovirus infection of isolated myocytes with a constitutively active PAK1 construct decreased the overall phosphorylation status of cTnI and increased the Ca 2þ sensitivity of force production. 55 Because phosphorylation status of individual cTnI sites was not assessed in that study, it is not known if some sites underwent increased phosphorylation while others exhibited a proportionally greater decrease in dephosphorylation. Alternatively, different isoforms of PAK may have different effects on cTnI phosphorylation.…”
Section: Physiological Implications Of Phosphorylation At Ser22ser23 mentioning
confidence: 99%